Unison Infestation: A Rare Case of Norwegian Scabies in a Mother-Baby Dyad - Laili, Fahmiatul; Dian Amelia Abdi; Setia Budi Salekede (Archives of The Medicine and Case Reports, 2024)
Norwegian scabies, also known as crusted scabies, is an uncommon but highly contagious skin disease caused by an infestation of the Sarcoptes scabiei mite. It is characterized by extensive crusting and scaling of the skin, often accompanied by intense itching. Norwegian scabies is typically seen in individuals with weakened immune systems or those who are unable to care for themselves properly. We reported a case of Norwegian scabies in a 33-year-old mother and her 9-month-old baby. The mother's symptoms began during her third trimester of pregnancy, and the baby became infected a few months after birth. Both patients presented with generalized pruritus and characteristic skin lesions. The baby was also found to be severely malnourished. In conclusion, this case highlights the importance of early diagnosis and treatment of Norwegian scabies, especially in vulnerable populations. Prompt and effective management can prevent complications and improve the quality of life for affected individuals.